Confiabilidade da avaliação do arremesso de 7 metros e influência do desempenho muscular dos segmentos do membro superior de atletas de handebol - Coelho, Victor Machado (Universidade Federal de São Carlos, 2025)
Handball is a team sport characterized by high intensity, physical contact, and complex technical movements such as throwing, passing, and directional changes. Among these, the throw—particularly the jump shot—is fundamental for goal scoring, relying on the proximal-to-distal sequence of the upper limb. Biomechanics plays a critical role in throwing performance by influencing both speed and accuracy, which are essential for success in the sport. While factors such as muscle strength, motor coordination, and tactical elements are recognized as key determinants of throwing effectiveness, the specific contribution of each upper limb segment remains unclear. This knowledge is crucial for optimizing training and rehabilitation protocols. Additionally, given the importance of throwing speed for performance, its assessment should be conducted regularly. However, the high cost of evaluation tools such as kinematic systems and sports radars limits their accessibility in low- and middle-income countries, such as Brazil. In this context, an alternative solution involves the use of video recording with low-cost cameras. This dissertation aimed to address two main objectives: (1) to investigate the intra- and inter-rater reliability of measuring throwing speed in the 7-meter shot using low-cost video cameras, and (2) to evaluate the influence of strength, power, and total work of each upper limb segment (shoulder, elbow, wrist), as well as handgrip strength, on throwing speed. Two studies were conducted to achieve these objectives. In Study 1, handball players aged 18 to 40 years participated to assess the reliability and validity of throwing speed measurement using low-cost video cameras. Intra- and inter-rater reliability was analyzed using the Intraclass Correlation Coefficient (ICC), and excellent reliability was found. Furthermore, strong correlations were observed between the video analysis results and physical performance tests, such as the Seated Medicine Ball Throw Test (MBT) and the Unilateral Seated Shot-Put Test (USSPT). These findings support the use of low-cost video cameras for reliably assessing throwing speed in handball players. In Study 2, the same group of athletes participated, and the specific contribution of each upper limb segment to throwing speed was analyzed. The 7-meter shot was evaluated as in Study 1, while concentric strength of the shoulder, elbow, and wrist was assessed to calculate peak torque, total work, and power. Handgrip strength was also measured. A Principal Component Analysis (PCA) revealed that shoulder biomechanics accounted for the greatest variability in throwing speed. However, the elbow and wrist also contributed, serving as complementary segments that refined the final movement adjustments to maximize speed. These results emphasize the biomechanical importance of each segment in throwing performance and suggest practical implications for training and rehabilitation protocols aimed at improving handball performance.
Reliability of the 7-meter throw assessment ande the influence of muscular performace of upper limb segments inhandball athletes
Keywords: Analise de componente principal; Ombro; Punho; Cotovelo; Fisioterapia; Principal Component Analysis; Shoulder; Elbow; Wrist; Physiotherapy; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA